2016
DOI: 10.1016/j.envpol.2015.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic analysis revealed highly diverse microbial arsenic metabolism genes in paddy soils with low-arsenic contents

Abstract: a b s t r a c tMicrobe-mediated arsenic (As) metabolism plays a critical role in global As cycle, and As metabolism involves different types of genes encoding proteins facilitating its biotransformation and transportation processes. Here, we used metagenomic analysis based on high-throughput sequencing and constructed As metabolism protein databases to analyze As metabolism genes in five paddy soils with low-As contents. The results showed that highly diverse As metabolism genes were present in these paddy soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(81 citation statements)
references
References 43 publications
8
73
0
Order By: Relevance
“…Zhang et al [41] revealed a strong correlation between arsC and arsM gene copies based on quantitative PCR, and suggested that similar compositions of microbial communities were involved in As(V) reduction and As(III) methylation in paddy soils. Previous studies revealed that the As(V) reduction, As(III) oxidation, and As(III) methylation processes co-exist and are closely related in microbes in paddy soils [4143]. Similarly, significant correlations between the structures of the ars , aioB , and arsM genes were also observed in this study, suggesting that these different As transformation systems co-exist and are closely related in microbes in both paddy and upland soil.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Zhang et al [41] revealed a strong correlation between arsC and arsM gene copies based on quantitative PCR, and suggested that similar compositions of microbial communities were involved in As(V) reduction and As(III) methylation in paddy soils. Previous studies revealed that the As(V) reduction, As(III) oxidation, and As(III) methylation processes co-exist and are closely related in microbes in paddy soils [4143]. Similarly, significant correlations between the structures of the ars , aioB , and arsM genes were also observed in this study, suggesting that these different As transformation systems co-exist and are closely related in microbes in both paddy and upland soil.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, in the soils studied, other soil properties such as pH represent additional stressors for microbial communities that may impact their diversity. Metagenomics studies also showed that microbial-mediated As metabolic processes in paddy soils correlated significantly with pH [40]. Zhang et al [41] revealed a strong correlation between arsC and arsM gene copies based on quantitative PCR, and suggested that similar compositions of microbial communities were involved in As(V) reduction and As(III) methylation in paddy soils.…”
Section: Discussionmentioning
confidence: 99%
“…This approach measures the presence and expression of specific genes, rather than attempting to isolate and study the microbes that carry them, 98% of which – it is estimated - do not grow in culture 134 . Microbially mediated arsenic metabolic processes that play a major role in arsenic cycling in agronomic systems include arsenite oxidation (via the aio genes), arsenate respiration (via the arr genes), arsenate reduction (via the ars genes) and arsenite methylation (via the arsM genes) 135 . Interested readers are referred to the recent excellent work of Andres and Bertin 132 for a comprehensive review of this subject.…”
Section: Rhizosphere Processesmentioning
confidence: 99%
“…Assessments of As methylation in soils and other environments have been hindered partly by limited databases for taxonomic classification. 20,21,49 The more extensive 726 protein sequence database developed for this study, along with a primer pair having greater degeneracy to amplify a broad range of arsM sequences, has enabled a deeper examination of arsM phylogenetic diversity. This study demonstrates the utility of these new tools, in conjunction with analyses of physiological responses to As, in probing relationships between community structure and biomethylation function.…”
Section: Environmental Science and Technologymentioning
confidence: 99%